Formulasi Detergen Cair Ekstrak Buah Pedada (Sonneratia alba) : Liquid Detergent Formulation of Pedada Fruit Ethanol Extract (Sonneratia alba J. Smith) - Rina Syafitri; Deri Anggraini; Mohamad Gazali; Selvi Mardalena; Ropita Ropita; Farah Salsabila; Irnu Alfarisi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
The pedada fruit extract (Sonneratia alba) contains saponin compounds which can be used as a natural foam in liquid detergents. The purpose of this study was to determine the effectiveness of pedada fruit extract as an additive to produce natural detergents that are environmentally friendly according to the Indonesian National Standard (SNI). This research consisted of preparation and extraction of pedada fruit with 96% ethanol, preparation of liquid detergent, and characterization the physical properties of liquid detergent. The formulation of liquid detergent used three treatments of adding pedada fruit extract, namely the addition of 5% (F1), 10% (F2), and 15% (F3). Data analysis used a completely randomized design (CRD) with one factor, namely the difference in the addition of pedada fruit extract to liquid detergent. The analysis was carried out in two repetitions. The results showed that the ethanol extract of pedada fruit was detected contain saponins. The treatment with ethanol extract of 5% (F1) is closest to the requirements of SNI 06-4075-1996 for liquid detergent with a pH value of 8.29 ± 0.04, viscosity of 37.7 ± 1.55 cPs, foam height of 2.5 cm, foam stability was 88.5±0.70%, specific gravity was 2.6±0.14 g/mL, and sedimentation volume was 0.975±0.021 mL.